ОЦІНКА ФІСКАЛЬНОГО ПРОСТОРУ МІСЦЕВИХ БЮДЖЕТІВ У КОНТЕКСТІ РОЗВИТКУ РЕГІОНІВ УКРАЇНИ - Хом'як, Мирослав Степанович (Науковий журнал «Світ фінансів», 2017)
Хом’як М. С. Оцінка фіскального простору місцевих бюджетів у контексті розвитку регіонів України. Здійснено оцінку фіскального простору місцевих бюджетів України на основі визначення податкового потенціалу регіонів і дослідження структури їх видатків. На прикладі України застосовано економетричний підхід, що дає змогу здійснити емпіричну оцінку фіскального простору регіонів на основі їх економічних показників. Встановлено, що найбільший фіскальний простір притаманний регіонам, які є менш промислово розвиненими. Доведено, що регіони з низьким рівнем фіскального простору та податкового потенціалу змушені формувати борги для вирішення власних фінансово-економічних проблем. Хомяк М. С. Оценка фискального пространства местных бюджетов в контексте развития регионов Украины. Осуществлена оценка фискального пространства местных бюджетов Украины на основе определения налогового потенциала регионов и исследования структуры их расходов. На примере Украины применен эконометрический подход, позволяющий провести эмпирическую оценку фискального пространства регионов на основе их экономических показателей. Установлено, что наибольшее фискальное пространство присуще регионам, которые являются менее промышленно развитыми. Доказано, что регионы с низким уровнем фискального пространства и налогового потенциала вынуждены формировать долги для решения собственных финансово-экономических проблем. Khomiak M. Estimation of fiscal space of local budgets in the context of Ukrainian regions development. Introduction. Fiscal decentralization, which is now actively being implemented in Ukraine, provides for increasing the level of fiscal autonomy of local budgets. In this context, it is necessary to assess the real possibilities of local governments to form a fiscal space, which should be understood as the ability to generate income and to implement rational expenditure in order to achieve regional development goals. Purpose. The goal of the article is a quantitative assessment of the fiscal space of local budgets to identify promising areas of fiscal decentralization in Ukraine. Methods. The theoretical basis of the article consists of foreign and domestic academic literature. As a methodological basis are used panel regressions for estimating the tax potential of regions and methods of structural analysis and comparisons - for investigation of trends in local budgets. Results. Formation of the fiscal space of local budgets in the article interpreted as a combination of realization of tax potential and restructuring of expenditures of local budgets. By using panel regressions are identified the regions with the highest tax potential. Based on studying the structure of local budget expenditures revealed that by highest fiscal space are characterized areas where industry is less developed and which are considered less economically successful. Conclusions. The study revealed that regions with low fiscal space and tax potential are forced to generate debt for solving their own financial and economic problems, while regions with high tax potential and greater fiscal space receive significant amounts of intergovernmental transfers and do not form a municipal debt. Despite this, was justified the necessity of the transition to a redistribution of financial resources on the goal-basis principle.